2014
DOI: 10.1038/onc.2014.398
|View full text |Cite
|
Sign up to set email alerts
|

Abrogation of protein phosphatase 6 promotes skin carcinogenesis induced by DMBA

Abstract: Somatic mutations in the gene encoding the catalytic subunit of protein phosphatase 6 (Ppp6c) have been identified in malignant melanoma and are thought to function as a driver in B-raf- or N-ras-driven tumorigenesis. To assess the role of Ppp6c in carcinogenesis, we generated skin keratinocyte-specific Ppp6c conditional knockout mice and performed two-stage skin carcinogenesis analysis. Ppp6c deficiency induced papilloma formation with 7,12-dimethylbenz (a) anthracene (DMBA) only, and development of those pap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
49
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(52 citation statements)
references
References 35 publications
3
49
0
Order By: Relevance
“…We found that a single 7,12-dimethylbenz(a)anthracene (DMBA) application was sufficient to produce papillomas in Ppp6c-deficient skin and showed that tumor promotion associated with Ppp6c-deficiency is more robust than that seen after repeated applications of a typical tumor promoter such as TPA. As such, ours was the first report that Ppp6c loss-offunction acts as a tumor promoter in mice [17]. However, it remained unclear whether tumor promotion (1) is specific to DMBA as an initiator or (2) is limited to papilloma or carcinoma formation.…”
Section: Introductionmentioning
confidence: 94%
See 4 more Smart Citations
“…We found that a single 7,12-dimethylbenz(a)anthracene (DMBA) application was sufficient to produce papillomas in Ppp6c-deficient skin and showed that tumor promotion associated with Ppp6c-deficiency is more robust than that seen after repeated applications of a typical tumor promoter such as TPA. As such, ours was the first report that Ppp6c loss-offunction acts as a tumor promoter in mice [17]. However, it remained unclear whether tumor promotion (1) is specific to DMBA as an initiator or (2) is limited to papilloma or carcinoma formation.…”
Section: Introductionmentioning
confidence: 94%
“…Mice exhibiting epidermal-specific, inducible Ppp6c deficiency (K14-CreER tam ; Ppp6c flox/flox ) were generated as described [17]. In brief, K14-CreER tam mice were crossed with Ppp6c-floxed (Ppp6c flox/flox ) mice (Accession No.…”
Section: Generation Of Knockout Micementioning
confidence: 99%
See 3 more Smart Citations